The Turkish version of the childhood bladder and bowel dysfunction questionnaire (CBBDQ): Cross–cultural adaptation, reliability and construct validity - Aydın, Gamze; van Engelenburg - van Lonkhuyzen, Marieke L.; Baktır, Seda; Kaya Mutlu, Ebru; Mutlu, Caner; de Bie, Rob A. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Bladder and bowel dysfunction (BBD) are both prevalent health problems in pediatric population. The CBBDQ is a parent-reported tool to evaluate and quantitatively assess bladder and bowel dysfunction symptoms in pediatric patients. This study was designed for the translation the CBBDQ into Turkish and the cultural adaptation of CBBDQ for the use among 5-12-year-old children. Moreover, another aim of this study was that the determination of the reliability and construct validity of the Turkish version. The main hypothesis of our study was that the translation and cultural adaptation of the CBBDQ into Turkish language, so that Turkish parents could understand it. Additionally, we estimated that the Turkish version would have eventual internal consistency and test-retest reliability and admissible construct validity. Materials and Methods: The CBBDQ was guideline driven translated into Turkish language and administered two times to the parents of children with one week interval to assess test-retest reliability. The internal consistency was determined by using Cronbach’s α value and the test-retest reliability was calculated by using the inter-rater correlation coefficient. For the estimation of construct validity, the Dysfunctional Voiding and Incontinence Scoring System (DVISS) and Pediatric Quality of Life Inventory (PedsQL) in 5-7, 8-12 years old children were used as the external criterias. Results: The participants were parents of 5-12-year-old children. The internal consistency was 0.83 that was the Cronbach’s α value which reflects a good result. The Turkish-CBBDQ5-12y and the DVISS showed a satisfactory level correlation (r=0.64 P<0.001). There was not any correlation between the Turkish-CBBDQ5-12y and the PedsQL-General Health and PedsQL-Psychological Health (r=-0.17, P=0.1 and r:0.12 P=0.25, respectively). Conclusion: The Turkish-CBBDQ5-12y version is a reliable and valid instrument in terms of the content and construction and can be confidently used in clinical practice.